Selected storage space requirements of University of the Philippines faculty homemakers - Agcaoili, Rosario Castro 1929- (1965)
In this study, an attempt was made to determine some of the storage space requirements of faculty homemakers living in the University of the Philippines Campus, Diliman, Quezon City, and to develop a functional, economical, and flexible design for the storage of household articles generally sued in four activities conducted in the home: cooking, dining, cleaning, and studying. Thirty-one homemaker were selected and interviewed on the basis of predetermines criteria such as possession of faculty rank by the homemaker or by her husband, at least one child ion both elementary and high school levels and at least one hosehold helper, and a minimum annual salary income of four thousand four hundred forty pesos(Php 4,440.00). Data on the homemaker's average height and work curves; occupation; housing values; household size and composition; annual salary income; marketing and storage practices as well as types and quantity of supplies commonly stored for cooking, dining, cleaning, and studying, served as guides in designing functional, economical, and flexible storage units. Factors found to affect storage needs included: occupation, size, composition, income of household members, and housing values. Storage space requirements were based on average figures for the homemakers in terms of body height, and household size, while modal figures were obtained for income size as well as for vertical and horizontal arm reaches. Storage space planned for a homemaker 5'2'' tall, with a household of eight, some of whom are of elementary and high school age; having an annual salary income of not less than Php 4,440.00, should be adequate to store 100 food items which would be utilized in a week's time; 102 utensils assigned to the mix, sink, range, and serve centers in terms of first-use; 428 items of china, glassware, silverware, and table linens; and 31 cleaning equipment and supplies. No numerical estimate of the number of study equipment and supplies in a home was made as it would be extremely difficult to ascertain how many books school supplies, magazines, and newspapers were commonly stored. Modular dimensions were used in designing the storage units to enable the homemaker to expand the basic designs in multiples of four when the need arose. Flexibility of design was considered so that the homemakers outside the population studied could also benefit from the findings. Inasmuch as this study has pointed to the need for more adequate and livable homes with adequate storage space, it is recommended that further study be made o the following: 1) A similar study of storage requirements with a more intensive inquiry into the needs, goals, and values of homemakers so as to develop such designs for storage facilities that result in even greater satisfaction to the individuals that use them. This is based on the premise that carefully planned, and intelligently organized storage spaces contribute significantly to good management and harmony in living, 2) Storage space requirements of other activities conducted in the home not covered by this study like those of laundering, dressing, child care, and sleeping. Such study will not only provide basic facts on measurements useful to homemakers, architects, and builders, but may also open up a broad field for the study of new uses and arrangements of storage units.